Prenatal and Neonatal MRI of Sacrococcygeal Teratoma With Surgical Correlation - Mahmood, Ali (Radiol Case Rep, 2015)
We report a case in which a sacrococcygeal teratoma was identified and characterized on prenatal and postnatal MRI, and correlated with subsequent surgical resection.